GENDER AND FINANCIAL REWARDS: ACCOUNTING STUDENTS' INTEREST IN A CAREER AS A PUBLIC ACCOUNTANT - Hasibuan, Abdul Nasser; Azim, Nik Mohd; Hardana, Ali; Nasution, Ananda Anugrah (Fakultas Ekonomi Dan Bisnis Islam IAIN Metro, 2024)
The choice of operators that can be taken as someone who has an accounting education background, namely public accountants, government accountants, corporate accountants, and educator accountants. The difference in career choices is where accountants work. Public Accountants are independent accountants who work for the public interest. This research is empirical research with a quantitative approach that involves the use of statistical analysis. The study used primary data, the research sample consisted of 160 accounting students from 1 PTN and 3 PTS. The tool used in the research was logistic regression with SPSS software version 16. Research explains gender influences the intention of accounting students in for a career as a Public Accountant. However, consideration of financial rewards and the job market has not been able to provide empirical evidence of interest in accounting students for a career as a Public Accountant.